Cultivation trials on Pleurotus sajor-caju (Fr.) Singer on sodium hydroxide pretreated sugarcane by-products - S, Chandrashekar B; Savalgi, Veena; Kulkarni, J H (Mushroom Research, 2015)
Please see the full text